Bangladesh - Education Development Index - World Bank (Washington, DC, 2013)
The study aims at developing an Educational Development Index (EDI) for Bangladesh. The present effort is the crucial first step towards developing a comprehensive and composite index of educational performance in Bangladesh. While the broader objective of the activity is to facilitate the decision making process for resource allocation and policy directions, the primary objective is to monitor progress in the primary education sector for district/upazila comparisons for better decision making processes. The exercise has been considerably constrained by the lack of dependable robust data. This report will make the policymakers aware of the need and importance of collection of reliable and more comprehensive information on a regular basis. The paper is organized as follows: as the main goal of this report is to develop a procedure for creating an Education Development Index (EDI) for the primary education sector of Bangladesh, the methodology is described in details with justifications of several steps in the section two. Sources of information and limitations are also discussed in this section. A description of the primary education sector of Bangladesh is given in section three. Section four presents the results and also explains how these results should be interpreted. Section five is the conclusion and recommendations. In addition, there are several annexes that include detailed results including upazila and district lists with ranks, a technical detail of the Principal Component Analysis (PCA), a step-by-step example of how an EDI can be constructed and a brief description of the stakeholder workshop that was organized at the beginning of the task to discuss the methodology with relevant stakeholders.